Environmental issues and economic decisions in developing countries. - MUNASINGHE, Mohan (1993)
Describes the role of environmental economics in bridging the gap between conventional decision-making and the new, more environmentally sensitive approach. Focuses on concepts and techniques for valuation of environmental costs and benefits. Concludes that there should be greater application of these concepts and techniques to practical problems in a developing country rather than further theoretical development.